Segmentation of markets in Central and Eastern Europe countrieswith the use of the CMS method - Salamaga, Marcin (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The paper is aimed at a comparative analysis of Central and Eastern European countries regarding the range of effects associated with changes in their exports. The effects of changes in the exports of individual countries will be separated based on the model of constant market share (CMS) developed by Leamer and Stern. The calculated effects: the demand effect, the market distribution effect, the commodity composition effect and the competitiveness effect will enable a detailed assessment of the sources of changes occurring in the exports of individual countries and will, in particular, allow for answering the following question: to what extent may changes in exports be explained by the economic situation in the world trade of individual clusters of commodities, and to what extent do they result from the competitiveness of these countries? The application of the multivariate statistical analysis method for the designated effects will allow for the identification of clusters of countries in a very similar position in the spatial and commodity arrangement, including countries of similar competitiveness of trade.
Mathematical Economics; 2017; Nr 13 (20); s. 67-78
Keywords: decision trees; logistic regression; turnover intention